Mabel Jones and the Doomsday Book - Mabbitt, Will; Collins, Ross (New York : Viking, 2016)
Mabel Jones and her pirate crewmates race an elusive creature known as Von Klaar to find the Doomsday Book, a guidebook used to wipe out humanity
Includes Q & A with the narrator
Ages 8-12
Keywords: Pirates -- Juvenile fiction; Fantasy -- Juvenile fiction; Adventure stories; Adventure and adventurers -- Fiction; Pirates -- Fiction; Fantasy; Fantasy fiction